Antibody targeting of CD24 efficiently retards growth and influences cytokine milieu in experimental carcinomas - Salnikov, Alexey V.; Bretz, N. P.; Perne, C.; Hazin, J.; Keller, S.; Fogel, M.; Herr, Ingrid; Schlange, T.; Moldenhauer, Gerhard; Altevogt, Peter (British journal of cancer, 2013)
The targeting of cancer stem cells by monoclonal antibodies offers new options for therapy. CD24 is a glycosylphosphatidylinositol-anchored membrane protein with a small protein core and a high level of glycosylation. It is overexpressed in many human carcinomas and is correlated with poor prognosis. CD24 is a marker for pancreatic and ovarian cancer stem cells, whereas breast cancer stem cells are negative for CD24. In cancer cell lines, changes of CD24 expression can alter cellular properties in vitro and tumour growth in vivo. We have shown before that monotherapy with monoclonal antibody (mAb) SWA11 to CD24 effectively retarded tumour growth in xenotransplanted mice.
Gesehen am 27.01.2022